2013
DOI: 10.1186/1556-276x-8-93
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of silver nanoparticle/chitosan composites against H1N1 influenza A virus

Abstract: Silver nanoparticle (Ag NP)/chitosan (Ch) composites with antiviral activity against H1N1 influenza A virus were prepared. The Ag NP/Ch composites were obtained as yellow or brown floc-like powders following reaction at room temperature in aqueous medium. Ag NPs (3.5, 6.5, and 12.9 nm average diameters) were embedded into the chitosan matrix without aggregation or size alternation. The antiviral activity of the Ag NP/Ch composites was evaluated by comparing the TCID50 ratio of viral suspensions treated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
194
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(201 citation statements)
references
References 26 publications
5
194
0
2
Order By: Relevance
“…Furthermore, the performed studies of antiviral action of various nanoparticles show that the higher the nanoparticle concentration, the higher their antiviral and antimicrobial effect [8][9][10][11][12]. Thus, the results are in good agreement with the results of biomedical experiments.…”
Section: Semiconductor Physics Quantumsupporting
confidence: 65%
See 1 more Smart Citation
“…Furthermore, the performed studies of antiviral action of various nanoparticles show that the higher the nanoparticle concentration, the higher their antiviral and antimicrobial effect [8][9][10][11][12]. Thus, the results are in good agreement with the results of biomedical experiments.…”
Section: Semiconductor Physics Quantumsupporting
confidence: 65%
“…It is well known that the samples with nanoparticles have antiviral and antimicrobial effect [8][9][10][11][12]. Furthermore, the performed studies of antiviral action of various nanoparticles show that the higher the nanoparticle concentration, the higher their antiviral and antimicrobial effect [8][9][10][11][12].…”
Section: Semiconductor Physics Quantummentioning
confidence: 99%
“…Park et al (2014) demonstrated that magnetic hybrid colloid decorated with AgNP (AgNP@MHCs) is able to inactivate bacteriophage ΦX174, murine norovirus (MNV), and adenovirus serotype 2 (AdV2). Mori et al (2013) proved antiviral activity of AgNP/chitosan composites against H1N1 influenza A virus. Lara et al (2010) reported that AgNP exert anti-viral activity against HIV-1 at an early stage of viral replication, since AgNP may act as inhibitors of viral entry.…”
Section: Den-2 Growth Inhibition Assaysmentioning
confidence: 95%
“…11,12 AgNPs are increasingly being explored as antiviral agents in viral illnesses, such as human immunodeficiency virus-1, hepatitis B virus, herpes simplex virus type 1, Monkeypox virus, and Tacaribe virus. [13][14][15][16][17] The mechanisms by which AgNPs exert their antiviral effects remain unclear.…”
mentioning
confidence: 99%